Borrelia burgdorferi in primary cutaneous lymphomas: a systematic review and meta‐analysis. (8th October 2020) - Travaglino, Antonio; Varricchio, Silvia; Pace, Mirella; Russo, Daniela; Picardi, Marco; Baldo, Antonello; Staibano, Stefania; Mascolo, Massimo
Summary: Background: The association between Borrelia burgdorferi and primary cutaneous lymphoma is still unclear. This systematic review and meta‐analysis aims to define the association of Borrelia burgdorferi with primary cutaneous lymphoma and its different entities. Methods: Electronic databases were searched for all studies that assessed the presence of Borrelia burgdorferi DNA in specimens of primary cutaneous lymphoma. The association between Borrelia and primary cutaneous lymphomas was assessed with an odds ratio (significant p < 0.05); cutaneous specimens with no lymphoproliferative disorders were used as controls. A secondary analysis was performed to assess the prevalence of Borrelia infection in different lymphoma entities. Results: Ten studies with 506 primary cutaneous lymphomas and 201 controls were included. The prevalence of Borrelia DNA positivity was highly heterogeneous among studies from different regions. Borrelia DNA positivity was significantly associated with primary cutaneous lymphomas (odds ratio = 10.88; p < 0.00001). The prevalence of Borrelia DNA positivity was similar among different entities (marginal zone: 7.3 %; follicular: 8.1 %; diffuse large B‐cell: 7.5 %; mycosis fungoides: 8 %). Conclusions: Borrelia burgdorferi is significantly associated with primary cutaneous lymphomas, with no differences among the several lymphoma entities (both B‐cell and T‐cell), but with strong geographical differences. Molecular testing for Borrelia would be justified in patients with primary cutaneous lymphoma from endemic areas.